Síntese e caracterização de MOFs e seus compósitos utilizados na modificação de eletrodos de carbono aplicados como sensores eletroquímicos - Fonseca, Ramon Raoni Ferreira da (2024)
The metal-organic frameworks (MOFs) MIL-53(Fe), MIL-88b-NH2(Fe), MIL-100(Fe) and MIL-82(Fe) were synthesized from the solvothermal reaction between a Fe salt and na acid ligand (benzene-1,4-dicarboxylic acid, 2-amino-benzene-1,4-dicarboxylic acid, benzene-1,3,5-tricarboxylic acid, or benzene-1,2,4,5-tetracarboxylic acid). All the materials obtained were characterized using physicochemical techniques. The electrochemical techniques showed that MIL-88b-NH2(Fe) had the most promising results for developing an electroanalytical methodology to detect and quantify Cu2+ in ethanol fuel. The presence of Cu2+ in ethanol fuel represents a problem in terms of quality, leading to malfunctioning automotive engines. Therefore, this study uses a FeIII-organic network to develop an innovative electrochemical sensor. Subsequently, the modified carbon paste selected to analyze Cu2+ in ethanol fuel was MIL-88b NH2(Fe) based on the results obtained from cyclic voltammetry and electrochemical impedance spectroscopy. Subsequently, square-wave anodic stripping voltammetry parameters were optimized using a design of experiments approach. The analytical signal of the electrode exhibited good stability (relative standard deviation = 5.2%). Besides, the correlation coefficient (r) and coefficient of determination (R²) calculated in the calibration curve were 0.9993 and 99.85%, respectively, indicating a good fit of the linear model to the experimental data. The limit of detection obtained from the linear equation was 2.0 × 10−8 mol L−1. Finally, in the recovery test using spiked samples of ethanol fuel, the obtained values were 83 and 96%, indicating the absence of matrix effects. It was shown that the MIL-88b-NH2(Fe) modified carbon paste electrode is a suitable sensor for assessing Cu2+ contamination in ethanol fuel under and above the limit permitted by Brazilian legislation.